Characterization of thin films of the solid electrolyte LixMg1−2xAl2+xO4 (x = 0, 0.05, 0.15, 0.25). Issue 43 (12th October 2015) - Put, Brecht; Vereecken, Philippe M.; Mees, Maarten J.; Rosciano, Fabio; Radu, Iuliana P.; Stesmans, Andre
Abstract : RF-sputtered thin films of spinel Li x Mg1−2 x Al2+ x O4 were investigated for use as solid electrolyte in Li-ion batteries. Abstract : RF-sputtered thin films of spinel Li x Mg1−2 x Al2+ x O4 were investigated for use as solid electrolyte. The usage of this material can enable the fabrication of a lattice matched battery stack, which is predicted to lead to superior battery performance. Spinel Li x Mg1−2 x Al2+ x O4 thin films, with stoichiometry ( x ) ranging between 0 and 0.25, were formed after a crystallization anneal as shown by X-ray diffraction and transmission electron microscopy. The stoichiometry of the films was evaluated by elastic recoil detection and Rutherford backscattering and found to be slightly aluminum rich. The excellent electronic insulation properties were confirmed by both current–voltage measurements as well as by copper plating tests. The electrochemical stability window of the material was probed using cyclic voltammetry. Lithium plating and stripping was observed together with the formation of a Li–Pt alloy, indicating that Li-ions passed through the film. This observation contradicted with impedance measurements at open circuit potential, which showed no apparent Li-ion conductivity of the film. Impedance spectroscopy as a function of potential showed the occurrence of Li-ion intercalation into the Li x Mg1−2 x Al2+ x O4 layers. When incorporating Li-ions in the material the ionic conductivity can be increased by 3 orders of magnitude. Therefore it is anticipated that the response of Li x Mg1−2 x Al2+ x O4 is more adequate for a buffer layer than as the solid electrolyte.